Ligand Recognition Determines the Role of Inhibitory B Cell Co-receptors in the Regulation of B Cell Homeostasis and Autoimmunity - Tsubata, Takeshi (Frontiers in Immunology, 2018)
B cells express various inhibitory co-receptors including CD22, CD72 and Siglec-G. These receptors contain immunoreceptor tyrosine-based inhibition motifs (ITIMs) in the cytoplasmic region. Although many of the inhibitory co-receptors negatively regulating BCR signaling by activating SH2-containing protein tyrosine phosphatase 1 (SHP-1), different inhibitory co-receptors have distinct functional properties. CD22, Siglec-G and CD72 preferentially regulate tonic signaling in conventional B cells, B-1 cell homeostasis, and development of lupus-like disease, respectively. CD72 recognizes RNA-related lupus self-antigen Sm/RNP as a ligand. This ligand recognition recruits CD72 to BCR in Sm/RNP-reactive B cells thereby suppressing production of anti-Sm/RNP autoantibody involved in the pathogenesis of lupus. In contrast, Siglec-G recognizes 2,3 as well as 2,6 sialic acids whereas CD22 recognizes 2,6 sialic acid alone. Because glycoproteins including BCR are dominantly glycosylated with 2,3 sialic acids in B-1 cells, Siglec-G but not CD22 recruits BCR as a ligand specifically in B-1 cells, and regulates B-1 cell homeostasis by suppressing BCR signaling in B-1 cells. Thus, recognition of distinct ligands determines functional properties of different inhibitory B cell co-receptors.